Program Pemulihan Ekosistem Gambut untuk Kesejahteraan Masyarakat di Desa Mantangai Tengah, Kecamatan Mantangai, Kabupaten Kapuas, Kalimantan Tengah - Rosana Elvince; Herwin Joni; Iis Yuanita; Sosilawaty Sosilawaty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The recovery of peat ecosystem program for community prosperity is known as Independent Village for Caring Peat. The implementation of this activity is a collaboration between the Ministry of Environment and Forestry by the Directorate of Peat Degradation Control, which the Directorate-General coordinates for Environmental Pollution and Degradation Control with the Faculty of Agriculture Palangka Raya University. Mantangai Tengah Village is one of the villages chosen as one of the village pilot projects under the Agriculture Faculty's supervision, Palangkaraya University. As Mantangai Tengah Village located in ex Mega Rice Project a million hectare. The program suggested to the village must be included in 3 programs (rewetting, revegetation, and revitalization). Those programs could help in recovery the degradation of peat ecosystem as a result of forest fire and increase village community incomes.